Liver Pathology in Autopsy Cases: A Retrospective Study in A Tertiary Care Center - Ekta Rani 1 , Sarita Nibhoria1 , Sanjay Kumar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Liver is the site of many diseases, many become symptomatic while few are diagnosed only on autopsy. The cause of chronic liver disease varies in different geographic areas and influenced by socioeconomic status, diet, life style and regional diseases. Method: This retrospective study was carried out in a tertiary care hospital in the department of pathology over a period of one year. A total of 40 cases of liver specimens, received as part of liver, constituted the material for the study. All were autopsy cases and the organs were received in 10% formalin. Routine grossing and staining with H&E stain were performed. Slides were analysed and the findings were noted in percentages. Results: A total of 40 specimens were studied. Age ranges from new born to 70 years, with 92.5 % male cases. 32.5% of cases were autolysed. 25% were showing chronic venous congestion followed by fatty change (22.5%), hepatitis (12.5%). 2.5% each of cirrhosis, steatohepatitis and normal liver. Conclusion: 1. Autopsy has an important role in identifying the cause of death. To overcome the autolysis of the specimen, the medical practitioner performing the autopsies should be trained about how to carry post mortem and to preserve the viscera for histopathological examination so that cause of death could be noted.